Hubungan Self-Esteem Dengan Student Well-Being Pada Siswa MTs Nurul Anwar di Kota Bekasi. - Nurfitriani, Aisyah; Fitriani, Yulia; Pertiwi, Yuarini Wahyu (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the relationship between Self-esteem and Student Well-being in MTs Nurul Anwar students in Bekasi City. The respondents of the study were 112 students, obtained using the cluster random sampling method. The instrument used in this study used a modified student well-being scale from Kurniastuti and Azwar and a modified self-esteem scale from Juju. There were 39 valid items from the student well-being scale, and 31 valid items from the self-esteem item. Data were collected using a questionnaire with Google Form and analyzed using the correlation method using IBM SPSS (Statistic Package for Social Science) 26 for Windows software. The results of the study showed that there was a positive relationship between self-esteem and student well-being, so that it can be interpreted that if students have high self-esteem, then student well-being in students will also be high. The categorization results show that student well-being is at a moderate level and self-esteem in students is at a high level. Suggestions for further researchers are to consider using different theoretical approaches and involving more diverse samples in order to see the consistency of the relationship between self-esteem and student well-being in several educational contexts and age ranges, such as in Senior High School (SMA).